99 Antibiotics-impregnated calcium sulfate in surgery: a case of broader use of innovative medical practice. (20th August 2018) - Drolet, Renée; Asselin, Geneviève; Nourissat, Alice; Coulombe, Martin; Rhainds, Marc
Abstract : Objectives: Surgical site infections (SSI) are a major source of mortality and morbidity, especially with prosthesis or medical implants. Prevention and control of SSI refer to numerous prophylactic measures, including administration of systemic antibiotic therapy. Local antibiotherapy mediated by bioresorbable bone substitute impregnated with antibiotics has been suggested as a complementary strategy. Beads of synthetic calcium sulfate (CaSO4 ) impregnated with antibiotics are prepared in the operating room and implemented at the surgical site to ensure local diffusion of antibiotics. A health technology assessment (HTA) was carried out in our university hospital to assess the effectiveness and safety of antibiotics-impregnated CaSO4 (AI-CaSO4 ) for the prevention and treatment of SSI in orthopedic, vascular and neuromodulation surgeries. Method: A literature review was conducted in several indexed databases and gray literature. Systematic review, primary studies, and guidelines on the efficacy and safety of AI-CaSO4 used for prevention or treatment of SSI in orthopedic, vascular or neuromodulation (neurostimulator implant) surgeries were retrieved. Two reviewers independently performed selection, quality assessment, and data extraction.The primary outcome was SSI. Secondary outcomes included infection eradication, time to eradicate infections and additional interventions related to infections. Data extraction from Electronic Patient Record (EPR) was performed to review local use. A cohort of 99 patients for whom AI-CaSO4 was used during orthopedic, vascular or neuromodulation surgeries between August 18 th 2015 and July 31 th 2018 was analyzed. Evidence-based review and local perspective were shared with an interdisciplinary group including orthopedic and vascular surgeons, pharmacists, infectiologists, and hospital managers. Results: Twenty-one studies on the efficacy of AI-CaSO4 were included. Available evidence suggests a beneficial effect of AI-CaSO4 in the surgical treatment of osteomyelitis whereas any conclusion can be drawn for other indications. There is insufficient evidence to support the use of AI-CaSO4 in the prevention of SSI. Few cases of hypercalcemia and renal insufficiency have been reported with AI-CaSO4 use. Data from 99 EPRs totaling 113 surgical procedures (orthopedic n=54, vascular n=37 and neuromodulation n=22) showed rapid adoption and broader use of with AI-CaSO4 since its introduction in 2015. Osteomyelitis treatment represents 2.7% of cases in our hospital. AI-CaSO4 was used mainly in the context of revision surgeries (74%) and prevention of SSI (65%). A lack of standardization for the preparation and documentation of the use of AI-CaSO4 was observed. Conclusions: Limited evidence supports the use of AI-CaSO4 in osteomyelitis treatment whereas safety profile remains to be proven. Broader indications with AI-CaSO4 use than those assessed in the literature, advocate for a better control and surveillance when a new medical practice is introduce in healthcare.